Sustainable use of biochar for resource recovery and pharmaceutical removal from human urine: A critical review - Masrura, Sayeda Ummeh; Dissanayake, Pavani; Sun, Yuqing; Ok, Yong Sik; Tsang, Daniel C. W.; Khan, Eakalak (Critical reviews in environmental science and technology, 2021)
Biochar has recently been used for recovering nutrients from waste streams including source-separated human urine. The increased consumption of pharmaceuticals has been a subject of concern as some of the compounds are not completely metabolized and consequently present in human urine. As urine contains both nutrients and pharmaceuticals, biochar applied for nutrient recovery may adsorb pharmaceuticals causing a concern on the introduction of the contaminants to the environment. This review article discusses the sorption of nutrients as well as pharmaceuticals by biochar. It reveals that biochars with different properties can be employed to separately attain nitrogen and phosphorus recovery, and removal of pharmaceuticals from source-separated urine. Production conditions including pyrolysis temperature and feedstock source are the vital aspects for delivering biochar properties that are suitable for different groups of chemical entities (nutrients versus pharmaceuticals). In addition, pharmaceutical adsorption is more favorable at lower solution pH whereas nutrient recovery is favorable at higher solution pH. If this concept of using separate biochars is employed, it will minimize the potential exposure of pharmaceuticals to the environment and humans and in the process the nutrient-rich biochar can be applied to the agrarian fields to achieve a closed-loop fertility system.